Low-order modelling of wake meandering behind turbines. (25th October 2019) - Gupta, Vikrant; Wan, Minping
Abstract : Based on recent numerical simulations and field experiments, the mechanism behind wake meandering is increasingly accepted to be through the amplification of upstream disturbances owing to the convectively unstable nature of the flow. In this paper, we deduce a low-order phenomenological model for the far-wake region, which is based on a modified form of the complex Ginzburg–Landau (CGL) equation for flows that are in the amplifier regime, i.e. are only convectively unstable. The model reproduces the main qualitative features of wake meandering: (i) its origin via amplification of upstream structures, (ii) dependence of oscillation frequency on the upstream disturbance amplitude (higher amplitudes lead to lower frequencies), (iii) shift towards lower frequencies as the wake flow evolves in the streamwise direction and, to an extent, (iv) the transfer of energy from very low frequencies towards relatively higher frequencies. Additionally, the model also predicts the increase in the meandering amplitude and an advancement in its onset with increasing thrust coefficient. To our knowledge, this is the first low-order dynamical system in the literature that models wake meandering. The model coefficients are obtained from the mean flow local stability results that we show correctly account for the changing operating conditions and thus pave way for the prediction of wake meandering features. Its low order makes it suitable to use inside an energy farm design model, where it can help to mitigate the adverse effects of wake meandering.